Polymyositis associated with hepatitis B: management with entacavir and prednisolone. - Wong, M.H.; Sockalingam, S.; Zain, A. (Blackwell Pub, 2011)
We report a 57-year-old woman with a 20-year history of hepatitis B presenting with progressive proximal lower limb weakness for the previous 1 month. Previous medical history included a pericardial and pleural effusion, of which no cause was found and pulmonary tuberculosis which has been adequately treated. Examination revealed multiple telangiactasia over face and nail beds and bilateral proximal lower limb weakness of power 4/5. Biochemical investigation revealed a raised erythrocyte sedimentation rate of 36 mm/h, elevated creatinine kinase levels (14 363 IU/L) and raised liver enzymes (alanine aminotransferase 445 IU/L, aspartate aminotransferase 606 IU/L) with high hepatitis B virus DNA (1 021 158 copies/mL). Nerve conduction tests and muscle biopsy were consistent with polymyositis. She received entacavir for hepatitis B treatment. Despite treatment with entacavir for 10 weeks, her weakness persisted and prednisolone was added. Upon commencement of prednisolone, her symptoms and biochemical profiles returned to normal.